Application, validation and comparison in different geographical contexts of an integrated model for the design of ecological networks - C.R. Fichera (Journal of Agricultural Engineering, 2013)
The issue of the fragmentation of natural habitats is increasingly at the core of the scientific debate, yet it is not taken into account in planning tools, with particular reference to the dynamism and complexity of landscapes. As it has been recognised at a European level, in order to enable different species to remain in good functional status, a network of green infrastructures is required. The concept of “ecological island” is no longer sufficient to adequately protect the fauna and the ecosystem it lives in. As a consequence, ecological islands must turn into ecological networks. The Ecological connectivity refers to the way habitats are physically connected to each other and how easy it is for species to move in. Good ecological connectivity is fundamental to the effective conservation of biodiversity considering that most species and ecological functions provided by ecosystems (ecosystem services) require a much wider space than that available within the boundaries of a single protected area. The main objective of this paper is to critically compare the application of a model for the design of ecological networks to two very different environmental contexts. This model was first tested in a Mediterranean area (the Province of Reggio Calabria) in 2008; the goal was to integrate the traditional (physiographic and functional) approaches into the design of ecological networks by taking into account biological and orographic elements as well as the anthropic structure of the territory. In 2011, within the ECONNECT European project, the model was applied to the pilot region of South-Western Alps (including the French region of Provence-Alpes - Côte d’Azur and the Italian regions Piedmont and Liguria), which is one of the richest transnational districts in Europe in terms of biodiversity. In such a region, the issue of multidisciplinary ecological connectivity was tackled in order to provide a series of proposals aiming at the development of the ecological potential of the area. The two applications allowed to further investigate the strengths and weaknesses of the implemented model by integrating its validation with information on faunal presence, which obviated one of the major limitations occurred in the first application.